1805 Va. Acts 51, An Act Concerning Free Negroes and Mulatoes - (:unkn) unknown (General Publisher, 1805)
That no free negro or mulato shall be suffered to keep or carry any firelock of any kind… without first obtaining a license from the court…
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES